1980
DOI: 10.1128/iai.27.2.449-454.1980
|View full text |Cite
|
Sign up to set email alerts
|

Mucin model for group B type III streptococcal infection in mice

Abstract: An experimental murine infection was established by the intraperitoneal injection of a log-phase culture of a laboratory reference strain of Streptococcus agalactiae, Lancefield group B, type III (strain SS620), suspended in sterile hog gastric mucin. The enhancement of streptococcal virulence was measured by a significantly increased mortality in outbred ICR Swiss mice. An inbred C57BL6 strain of mice was resistant to the mucin-bacterial combination. Mucin, treated with Desferal to chelate the iron, did not l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1982
1982
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Male C3H/HeN mice, 13-wk-old and ~30 g, were obtained from the National Cancer Institute. The mucin model of Fleming (9,10) was used in all experiments. A 10% (wt/vol) suspension of type II hog gastric mucin (Sigma Chemical Co.) in Dulbecco's balanced salt solution was prepared and autoclaved.…”
Section: Methodsmentioning
confidence: 99%
“…Male C3H/HeN mice, 13-wk-old and ~30 g, were obtained from the National Cancer Institute. The mucin model of Fleming (9,10) was used in all experiments. A 10% (wt/vol) suspension of type II hog gastric mucin (Sigma Chemical Co.) in Dulbecco's balanced salt solution was prepared and autoclaved.…”
Section: Methodsmentioning
confidence: 99%
“…1D), suggesting that the mucin-enhanced virulence in A. baumannii is not restricted to BALB/c mice. In this regard, other mouse strains, such as ICR-Swiss, Swiss White, and CF-1, previously have been used in similar models (16,18,19,26), although actual magnitudes of the enhancement in some of those studies had not been reported in detail.…”
Section: Resultsmentioning
confidence: 99%
“…Enhancement of in vivo bacterial virulence and infection by porcine mucin is not a phenomenon unique to A. baumannii. Indeed, mucin enhances the infection or virulence of a wide range of Gram-positive and -negative bacteria, although the magnitude of the effect varies from bacterium to bacterium and even from isolate to isolate (15)(16)(17)(18)(19). Apart from intraperitoneal inoculation, admixture of mucin with bacterial inoculum has also been applied to enhance other routes (intranasal [i.n.…”
mentioning
confidence: 99%
“…Bacterial strain variation in mouse lethality tests. Using the laboratory reference strain (SS620) from previous studies (10) and the clinical isolate (M732) of type III S. agalactiae, mucin was found to enhance the level of virulence for mice as measured by a reduction in the number of CFU required to produce an LD50. Although mucin lowered the LD50 significantly in both strains, M732 required more CFU (450) than the SS620 (93) ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Unprotected mice were given an i.p. injection of 107 colony-forming units (CFU) of SS620 GBS serotype III in either Todd-Hewitt broth (Difco) or 5% mucin (10). Subsequently, blood cultures were obtained from each of two mice at intervals of 0.25, 0.5, 0.75, 1, 2, and 20 h by aspiration of the capillary plexus behind the eye.…”
mentioning
confidence: 99%